2012
DOI: 10.1111/j.1469-7610.2012.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of ADHD in a general population of primary school children

Abstract: The findings in this general population sample with a strong general ADHD factor in the bifactor model supports the view on ADHD as a unitary concept with specific domain factors for inattention and impulsivity, but not for hyperactivity. The bifactor model questions the utility of constructing ADHD subscales by the use of a simple sum score when using the SNAP-IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 38 publications
12
60
0
Order By: Relevance
“…1d) similar to that of Ullebø et al [8], where the HY items were excluded from the specific factors. As seen in table 2, neither the incomplete bifactor model of the FBB-ADHS nor that of the SBB-ADHS exhibited a meaningful difference regarding model fit compared to the other bifactor models.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…1d) similar to that of Ullebø et al [8], where the HY items were excluded from the specific factors. As seen in table 2, neither the incomplete bifactor model of the FBB-ADHS nor that of the SBB-ADHS exhibited a meaningful difference regarding model fit compared to the other bifactor models.…”
Section: Resultsmentioning
confidence: 70%
“…Those studies have generated consistent proof of the superiority of bifactor models compared to models with correlated factors [4,5,6,7,8,9,10,11]. On top of that, they have found that the general factor explains much more variance than the specific factors, which calls the diagnostic procedure of both diagnostic manuals (DSM and ICD) into question (counting symptoms within the separate dimensions rather than over all items).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…43 The reliability has been very good to excellent. 44 A score ≥95th percentile has been shown to be closely associated with ADHD. 45 …”
Section: Autism Spectrum Screening Questionnairementioning
confidence: 99%
“…The child that gets an ADHD diagnoses fulfil at least six criteria in each group not related to another diagnosis and in different contexts before 7 years of age. Children with ADHD have difficulties in inhibitory control (Barkley, 1997;Senderecka, Grabowska, Szewczyk, Gerc, & Chmylak, 2012) which results in inattention and impulsivity (Breivik, Gillberg, Lundervold, & Posserud, 2012).…”
Section: Adhdmentioning
confidence: 99%